A natureza argumentativa da língua no discurso informativo da notícia - Freitas, Mara Rubia Rodrigues (2016)
Within the intersection of two perspectives, a journalistic one, emphasizing the objective effect, and another, linguistic, giving emphasis to the enunciative aspect of language, this dissertation aims at analyzing how intersubjectivity and argumentativeness build up meanings in the journalistic discourse, and at how objectivity can be constitutive of this construction. According to Pesquisa Brasileira de Mídia 2015, Brazilian readers keep up considering the newspaper a reliable source of information about daily life events, whether in their neighborhood or in the worldwide domain. Part of this reliability is the fruit of the press' discourse about itself: the discourse of trustworthiness to the facts, which speak for themselves, of the space of plurality of opinions in the name of impartiality as well as of objectivity. On the other hand, the Argumentation Within Language Theory (AWL) demonstrates that the meanings produced in the discourse are an intersubjective and an argumentative construction, considering that argumentativity is inherent to language, which is constitutive of any kind of discourse. According to the AWL, while words are in the virtuality of the linguistic system, they have potential meanings, orientations for the discursive continuum in certain directions. An argumentation consists of, according to the language possibilities, establishing a relation between words, by which the meaning of a word enunciated depends on the meaning of another word also enunciated. The intersubjectivity, within this approach, means that the speaker mobilizes the argumentative resources of the language to make up discursive objects according to multiple perspectives on objects of the factual reality. The speaker does not offer the interlocutor an objective representation of reality, but an argumentative apprehension of it, in order to discuss both.